The ABC's of Recovery Room Nursing - Johnson, Bev (Operating Room Nurses Association of Canada Journal, 1993)
The goal of providing safe, knowledgeable, compassionate and individualized nursing care to patients and their families, in the immediate post-anaesthetic period, is universal. The method of meeting that goal remains unique to the individual professional nurse and to her unit. AORN (1983) identified the following outcomes as speciﬁc to patients requiring post anaesthesia care: 1. Respiratory status ismaintained or improved. 2. Cardiovascular status is maintained or improved. 3. Fluid and electrolyte balance is maintained or improved. 4. Privacy and dignity are maintained. 5. The patient is protected from infection. 6. The patient has no adverse effects from lack of, or improper use of, safety measures. 7. The patient is as comfortable as possible. There is a growing awareness in the health care community of the role of the post anaesthesia nurse. Major and complicated surgical procedures are becoming more prevalent with each passing year and therefore, the patient is more prone to crisis in the post- operative period than at any other time throughout the surgical experience. Because of this, the recovery